Community-based participatory research with women in prison: the women’s words/women’s worlds peer mentoring program - Dewey, Susan (SpringerBriefs in anthropology, 2024)
Community Based Participatory Research (CBPR) An Innovative Approach to Working with Women’s Prisons -- Collaboratively Determining Direction and Parameters -- The Mentor and Mentee Manuals -- Implementation -- Ten Reasons Why Community Based Participatory Research Can Transform Women’s Prisons.